Mutations in known disease genes account for the majority of autosomal recessive retinal dystrophies. Issue 6 (3rd September 2018) - Patel, N.; Alkuraya, H.; Alzahrani, S.S.; Nowailaty, S.R.; Seidahmed, M.Z.; Alhemidan, A.; Ben‐Omran, T.; Ghazi, N.G.; Al‐Aqeel, A.; Al‐Owain, M.; Alzaidan, H.I.; Faqeih, E.; et al.
Abstract : Retinal dystrophies (RDs) are hereditary blinding eye conditions that are highly variable in their clinical presentation. The remarkable genetic heterogeneity that characterizes RD was a major challenge in establishing the molecular diagnosis in these patients until the recent advent of next‐generation sequencing. It remains unclear, however, what percentage of autosomal recessive RD remain undiagnosed when all established RD genes are sequenced. We enrolled 75 families in which RD segregates in an apparently autosomal recessive manner. We show that the yield of a multigene panel that contains known RD genes is 67.5%. The higher yield (82.3%) when whole exome sequencing was implemented instead was often due to hits in genes that were not included in the original design of the panel. We also show the value of homozygosity mapping even during the era of exome sequencing in uncovering cryptic mutations. In total, we describe 45 unique likely deleterious variants (of which 18 are novel including one deep intronic and one genomic deletion mutation). Our study suggests that the genetic heterogeneity of autosomal recessive RD is approaching saturation and that any new RD genes will probably account for only a minor role in the mutation burden. Abstract :